The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1089/end.2005.1130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulse Width on Object MovementIn VitroUsing Holmium:YAG Laser

Abstract: Pressure waves from Ho:YAG lithotripsy are less than with other modalities, yet some retropulsion occurs. The duration of the laser pulse can influence shockwave generation and object migration. Longer pulse width results in less object movement after one shock and more energy delivery during repetitive shocks. Clinically, this regimen may reduce the need for fiber readjustment and lead to more efficient stone fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…[19][20][21][22][23][24] The bubbles are larger than the fiber diameter and can extend from the fiber tip up to ∼2 mm depending on pulse rate and energy. The mechanical shockwaves created by the cavitation bubbles are not a major contributor to stone fragmentation at the 500-μs pulse duration used in this study, because the ablation mechanism is predominantly photothermal.…”
Section: Retropulsion and Flow Velocimetrymentioning
confidence: 99%
“…[19][20][21][22][23][24] The bubbles are larger than the fiber diameter and can extend from the fiber tip up to ∼2 mm depending on pulse rate and energy. The mechanical shockwaves created by the cavitation bubbles are not a major contributor to stone fragmentation at the 500-μs pulse duration used in this study, because the ablation mechanism is predominantly photothermal.…”
Section: Retropulsion and Flow Velocimetrymentioning
confidence: 99%
“…13,14 Furthermore, recent Ho:YAG laser lithotripsy retropulsion studies have concluded that the use of lower pulse energies, longer pulse durations, higher pulse rates, and smaller optical fiber diameters is the optimal combination of laser parameters for minimizing stone retropulsion. [15][16][17][18][19][20] A comprehensive study of all of these parameters was beyond the scope of this paper. However, it should be emphasized that, unlike the flashlamppumped Ho:YAG laser, the diode-pumped TFL is an ideal laser for operation within the range of laser parameters listed above, due to the TFL's excellent spatial beam profile that allows use of small-core fiber diameters and its operation at arbitrary pulse durations and pulse rates.…”
Section: Retropulsion Studiesmentioning
confidence: 99%
“…Previous Ho:YAG laser lithotripsy retropulsion studies also have reported that the use of lower pulse energies, longer pulse durations, higher pulse rates, and smaller optical fiber diameters is the optimal combination of laser parameters for minimizing stone retropulsion. [17][18][19][20][21][22] The TFL technology is ideally suited for operation with this combination of laser parameters.…”
Section: Stone Phantom Retropulsion Studiesmentioning
confidence: 99%